Optimization Of Terminal Facilities Management For Passenger Convenience At Radin Inten II Lampung International Airport - Siti Nur Annisa, Septiana; Iswahyudi, Prasetyo; Rinaldi, Ridho (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
Airport is infrastructure used to provide air flight services is. Radin Inten II International Airport is an airportmanaged by PT Angkasa Pura II. This study aims to determine whether the terminal of Lampung Radin Inten II International Airport has been optimized and in accordance with applicable regulations. So from this description, the author took the title "Optimization of Terminal Facility Management for Passenger Comfort at Radin Inten II International Airport Lampung". The formulation of the problem in this study is what are the facilities in the Terminal that support passenger comfort and how to optimize the management of terminal facilities for passenger comfort at Radin Inten II Lampung International Airport. Research Methods are qualitative descriptive methods, making observations in the airport terminal area, interviews, distributing questionnaires and literature studies and documentation of research objects. In the results of the study, there are still problems that there are still some facilities that are not in accordance with applicable regulations and can be optimized again to improve passenger comfort at Radin Inten II Lampung InternationalAirport. So that the conclusion that can be drawn in this study is the need to optimize the management of facilities in facilities that are not in accordance with the rules and facilities that can improve passenger comfort such as repairing facilities that are not in accordance with the rules, regulating temperature and ensuring the terminal area is clean